THEORY AND PRACTICE. - Oehler, Christian (The Accounting Review, 1942)
Abstract The subject of theory and practice in accounting is usually conceived as one of theory versus practice, thereby implying conflict rather than cooperation. It is a subject about which many misconceptions exist in the minds of those who have given no serious thought to the very close correlation between the two. It is probably not very far from the truth to assert that these misconceptions have arisen because of a failure to distinguish between the ability to accomplish a desired result and the scientific principles and rules of procedure in accordance with which the work must proceed if the desired result is to be obtained. there never can be any conflict. The theoretical aspect of accounting is that which views it as a science, albeit not an exact science (because of the human element) and the theories of accounting are nothing but principles expressing the result of the scientific analysis of the significance of the financial condition or the operating results of a business enterprise and of the methods needed in order that they may be properly expressed and interpreted. The practical aspect of accounting is that which views it as an art, viz., the practical application of the theories of accounting to the solution of the problems of business.